Hegel e o fim da arte na letra e no espírito - Guilherme Ferreira (2016)
This dissertation investigates the prediction of Hegel on the theme of "End of Art" presented in their aesthetic courses. In order to provide a broad reading on this subject, try - from concept art - highlight the various moments and art functions in all of the Hegelian system. Immersed in this jurisdiction, and followed the considerations about the concept of art, we try analyze the theme of the inflection points of the end of art in relation to classical art concepts and romantic art in order to accent their strong and weak senses the aesthetic framework of Hegel . In this direction, articulates the classic and romantic interpretation of ethics dessubstantialization art. On the other hand, the theme of the end of art, the strong sense of Hegelian letter focuses on the context of prosaic traits of modern culture, meaning that distends our interpretation for dessubstantialization, dematerialization and art poeticization. Therefore, from the positive sense of the art dissolution sought to verify, in general, the sense of spirit, aesthetic text heritage of Hegel to the contemporary artistic phenomenon.